Could cholesterol remnants predict long-term cardiovascular events after NSTACS?. (3rd October 2022) - Martinon-Martinez, J; Alvarez Alvarez, B; Gonzalez Ferrero, T; Garcia-Rodeja Arias, F; Otero Garcia, O; Jimenez Ramos, V; De La Fuente Rey, A; Cacho Antonio, C; Cid Alvarez, B; Iglesias Alvarez, D; Agra Bermejo, R; Rigueiro Veloso, P; et al.
Abstract: Introduction: The remnant cholesterol (RC) promotes atherosclerotic cardiovascular disease. However, the prognostic impact of elevated RC levels in patients with non-ST-elevation acute coronary syndrome have not been established in the current population. Then, our objetive is investigated the effect of RC in terms of long-term mortality in patients admitted for NSTACS Methods: This is an observational study in which we included all patients discharged from cardiology for ACS in two centers from 2003 to 2018. Patients were classified by low RC values <23 mg/dL or high RC values ≥24 mg/dL in the first blood count performed during hospitalization. We analyzed the effect of RC (continuous variable) on all-cause mortality, cardiovascular mortality and MACE using the Cox regression model adjusted for several confounding variables. Results: We included 5685 patients diagnosed with ACS, with a mean age of 66.50 (SD ±13.20) years, 27.1% female. The baseline, during admission and discharge characteristics are shown in table (1 and 2). During follow-up (median 56 months, IQR 21–79 months) there was an increased risk of all-cause mortality in patients with higher levels os RC unadjusted and adjusted for several factors (age, sex, GRACE, early coronariography, hypertension, treatment at discharge), HR (1.003, CI 1.000–1.005, p 0.003). Similar results were observed for cardiovascular mortality (HR 1.003, CI 1.000–1.006, p 0.003), and MACE (HR 1.002, CI 1.000–1.003, p 0.002) Conclusion: RC could have prognostic impact in the long-term follow up in patients with NSTACS, even after adjusting for risk factors and evidence-based treatments. There results should be taken under consideration for the treatment and management of NSTACS patients. Funding Acknowledgement: Type of funding sources: None.